2011
DOI: 10.1186/1471-2334-11-72
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic HPV among HIV infected female population in West Bengal, India

Abstract: BackgroundPrevalence of both cervical cancer and Human Immunodeficiency Virus (HIV) infection are very high in India. Natural history of Human Papilloma Virus (HPV) infection is known to be altered in HIV positive women and there is an increased possibility of persistence of HPV infections in this population. Therefore, this study was conducted to understand the epidemiology and circulating genotypes of oncogenic HPV among HIV positive and negative female population in West Bengal, India.MethodsIn this hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…In our study, the prevalence of HPV infection among HIV‐infected women was 57.7%. Studies done in India have found a varying prevalence of 26.4% to 56% . High‐risk HPV types are reportedly found in 37.3–59% of patients with HIV .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of HPV infection among HIV‐infected women was 57.7%. Studies done in India have found a varying prevalence of 26.4% to 56% . High‐risk HPV types are reportedly found in 37.3–59% of patients with HIV .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Eastern India [16] has also shown prevalence of HPV 16, 18 among HIV positive females from Kolkata (32.2%; n = 30) was higher than HIV negative females (9.1%; n = 101). About 53% (23/43) of cases with oncogenic HPV were infected with genotypes other than 16, 18 either as single/multiple infections.…”
Section: Discussionmentioning
confidence: 99%
“…Both vaccines have demonstrated high efficacy against precancerous lesions caused by 16/18 types of HPV. Gardasil, a quadrivalent human papillomavirus vaccine is designed based on HPV types 6,11,16,18. Cervarix is based on HPV types 16 and 18.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similar study by Sarkar et al (2011), risk becomes higher when age was more than 30. 4 According to present study lower genital tract infections were more prevalent in age group between 31-39 years. Probably this was related with declining body immunity as seen in more advanced HIV infected cases.…”
Section: Distribution Of Cases According To Agementioning
confidence: 96%
“…A hospital based study from the eastern part of India observed a prevalence of oncogenic HPV among HIV-positive women to be 46.2% whereas a study from northern India showed a prevalence of high-risk HPV in 20%. 4,5 Justification HIV positive women are at higher risk of developing reproductive tract infections as compared to HIV negative women. Large observational studies involving HIV positive women have demonstrated a strong and consistent association between confection with HIV, HPV and CIN.…”
Section: Introductionmentioning
confidence: 99%